2010
DOI: 10.1111/j.1365-2753.2010.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

From continuing education to personal digital assistants: what do physical therapists need to support evidence‐based practice in stroke management?

Abstract: Physical therapists prefer technology-assisted access to resources and education and favour attending multiple interactive, expert-facilitated education sessions incorporating opportunities for case-based learning and practice of new skills to change behaviour related to evidence-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
(65 reference statements)
1
31
0
4
Order By: Relevance
“…Participants suggested that CPGs might be more readily related to practice with interactive, expert-facilitated sessions for clinicians to review guidelines and brainstorm implementation. This preference for in-person sessions has also been identified in qualitative studies with occupational therapists and physiotherapists [51,52], and personal contact between researchers and decision makers is one of the most frequently advocated facilitators in the KTE literature [53,54]. Therefore a potential challenge for KTE is finding a balance between the distancing that occurs when research users are represented by associations, and the feasibility of consulting with individual clinicians.…”
Section: Discussionmentioning
confidence: 93%
“…Participants suggested that CPGs might be more readily related to practice with interactive, expert-facilitated sessions for clinicians to review guidelines and brainstorm implementation. This preference for in-person sessions has also been identified in qualitative studies with occupational therapists and physiotherapists [51,52], and personal contact between researchers and decision makers is one of the most frequently advocated facilitators in the KTE literature [53,54]. Therefore a potential challenge for KTE is finding a balance between the distancing that occurs when research users are represented by associations, and the feasibility of consulting with individual clinicians.…”
Section: Discussionmentioning
confidence: 93%
“…23 Salbach 20 notes that study therapists were most engaged in inter-active discussions and watching a patient care video demonstration. In our study, the sharing of practical experience and real world implementation discussions were highly rated by the PTs completing training evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions are described in Multimedia Appendices 8 and 9. Interventions using mobile communication technologies in both developed countries (Italy [205], US [1,92,206-228], UK [229-232], France [233], Canada [234-237], Japan [238], Australia [239], New Zealand [240], South Korea [241-245], and Denmark [246]), and developing ones (Thailand [247], Peru [248], Kenya [57,249,250], Taiwan [251,252], Israel [253-255], Uganda [256,257], Thailand [258], Singapore [259], Turkey [260], India [261], and South Africa [262]) have investigated the use of mobile phone-based apps, mobile phone voice call, SMS, and PDAs.…”
Section: Resultsmentioning
confidence: 99%